Revealing the degree and impact of inhomogeneous electrolyte distributions on silver based gas diffusion electrodes. (1st September 2021) - Röhe, Maximilian; Franzen, David; Kubannek, Fabian; Ellendorff, Barbara; Turek, Thomas; Krewer, Ulrike
Abstract: Silver based oxygen depolarized cathodes (ODC) are a promising technology to reduce the specific electrical energy demand of chlor-alkali electrolysis by around 30 %. Here we present the first modeling approach of an ODC for evaluating the influence of inhomogeneities on electrochemical performance and electrode dynamics. The focus is laid on the electrolyte distribution in the electrode because it is crucial for the gas-electrolyte interface and thus electrode performance and dynamics. To model the inhomogeneities, several one-dimensional three-phase models with different flooding degree of the electrode are coupled in parallel. The model is validated against polarization curves and electrochemical impedance spectra for ODC with silver content of 92, 97, 98 and 99 wt-% Ag. The electrochemical impedance spectroscopy measurements show flattened semicircles in the Nyquist plot with one apparent fast time constant, which ranges from 0.0015 s to 0.03 s depending on the respective ODC composition. The fast time constants result from electrochemical reaction and double layer; no time constant for a mass transport was identified. According to the simulations, the distorted form of the semi-circles is caused by local distribution of the liquid electrolyte within the ODC. It is revealed that there are strong gradients in local performance inside the electrode. Domains with a low intrusion of liquid electrolyte seem to be electrochemically highly active whereas flooded domains are almost inactive. The comparison of ODC with varying silver/polytetrafluoroethylene ratio suggests that the size and location of the gas-liquid interface, rather than the wetted catalyst surface area, is the key to achieving high ODC performance. We reveal that the electrochemical impedance spectroscopy is sensitive to the electrolyte distribution, while polarization curves do not contain sufficient information about the location and distribution of the electrolyte.